การประมาณค่ากำลังอัดของอิฐมวลเบาโดยใช้เครื่องกดไฮดรอลิกส์ขนาดเล็ก - บวรวุฒิ พรมถาวร (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
The aim of this research was to use compressive strength test on lightweight concrete block at curing time of 28 days from small hydraulic pressing machine. To use estimate compressive strength test at curing time of 7, 14 and 21 days. Referring to lightweight concrete block testing with small hydraulic pressing machine showed that that a cost effective size of the block when using a sample block with the dimensions of 7.5x20x60 centimeters cutting to dimensions of 7.5x7.5x7.5 centimeters with curing time at 7, 14, 21 and 28 days respectively A subsequent, test of the lightweight concrete block with sample dimension of 15x15x15 centimeters and curing time at 7, 14, 21 with 28 days respectively that are compressive strength testing by universal testing machine. Therefore, the researcher uses the compressive strength testing of lightweight concrete block of two machines to compare the compressive strength of lightweight concrete block from small hydraulic pressing machine and universal testing machine. The result of compressive strength with small hydraulic pressing machine is greater than compressive strength with universal testing machine. Nevertheless speed of cylinder of two machines has different speeds that affects compressive strength of lightweight concrete block and the compression ratio is 0.87. After that,